Biomechanical modelling of colorectal crypt formation and in-vitro replication - Nelson, Martin, R. (2011)
The colon's epithelial lining exhibits a number of invaginations into the underlying tissue, called the crypts of Lieberkühn. Housing stem cells at their bases, these crypts play an essential role in the maintenance of the epithelium; however, the processes by which crypts form are not conclusively understood. This study deploys mathematical and experimental modelling to validate one potential mechanism: that cellular growth in the developing epithelium causes a build up of compressive stresses, resulting in buckling instabilities which initiate crypt formation.